Adherence to Standards for Reporting Diagnostic Accuracy in Emergency Medicine Research. (26th July 2017) - Gallo, Lucas; Hua, Nadia; Mercuri, Mathew; Silveira, Angela; Worster, Andrew; ,
Abstract: Background: Diagnostic tests are used frequently in the emergency department (ED) to guide clinical decision making and, hence, influence clinical outcomes. The Standards for Reporting of Diagnostic Accuracy (STARD) criteria were developed to ensure that diagnostic test studies are performed and reported to best inform clinical decision making in the ED. Objective: The objective was to determine the extent to which diagnostic studies published in emergency medicine journals adhered to STARD 2003 criteria. Methods: Diagnostic studies published in eight MEDLINE‐listed, peer‐reviewed, emergency medicine journals over a 5‐year period were reviewed for compliance to STARD criteria. Results: A total of 12, 649 articles were screened and 114 studies were included in our study. Twenty percent of these were randomly selected for assessment using STARD 2003 criteria. Adherence to STARD 2003 reporting standards for each criteria ranged from 8.7% adherence (criteria—reporting adverse events from performing index test or reference standard) to 100% (multiple criteria). Conclusion: Just over half of STARD criteria are reported in more than 80% studies. As poorly reported studies may negatively impact their clinical usefulness, it is essential that studies of diagnostic test accuracy be performed and reported adequately. Future studies should assess whether studies have improved compliance with the STARD 2015 criteria amendment.